A study on failure mechanism of self-supported electric poles through full-scale field testing. (July 2017) - Vivek, B.; Sharma, S.; Raychowdhury, P.; Ray-Chaudhri, S.
Abstract: Self-supported single poles are widely used for transmission of electricity in rural areas of India. Recently, in Unnao District of Uttar Pradesh, India, a large number self-supported poles was found to suffer extensive tilting during wind storms. This incident has raised safety concerns for the Government as well as the company in charge of the construction and installation of the poles. These prestressed concrete poles of about 8.5m height were embedded in the ground by 1.5m as per standard practice. From visual inspection of the failure sites and a detailed geotechnical investigation of soil from 24 nearby boreholes, it seemed that the failures caused primarily due to inadequate resistance from the soft soil of Indo-Gangetic plain, resulting bearing and overturning failures. In order to understand further, a test setup was created at the Institute of Technology Kanpur, where the full-scale poles had been brought from Unnao and were erected in a specifically prepared soil pit to match the in-situ soil condition of the Unnao case-study sites. The poles were erected on compacted silty clay soil deposit by adopting standard procedure of back-filling as used in site. The poles were then subjected to lateral loading and unloading through a specially designed frame. The load capacities of the poles have been found to be in the range of 0.95 to 1.48 times the design wind load for the chosen sites. It is noted that by increasing the footing dimension by only 20%, the capacity of the pole is improved by about 54%. Further, it is also found that by replacing a concrete footing by a compacted brick-stone aggregate grouted footing (a common practice in rural India), no significant alteration in the load capacity or force-deformation behavior is observed. A numerical study was also conducted to understand the experimentally observed behavior. It is found from this study that the analytical model considering nonlinear soil–pole interaction (Case II) showed better prediction of experimental behavior than the fixed base model (Case I). Finally, a sensitivity analysis using First-Order-Second-Moment (FOSM) method indicated that cohesion influences the load capacity of the poles most significantly compared to other soil parameters such as friction angle, unit weight and shear modulus for the chosen soil type and available soil exploration data. Highlights: Full-scale field tests on 3 electric poles are done. Effect of foundation configuration and soil properties on failure mechanism are studied. Load capacities are compared with design wind load. Analytical model considering nonlinear soil–structure interaction captured the experimental behavior reasonably well. FOSM analysis indicated that cohesion is the most influencing parameter for available soil data.